Embodied techno-space: An auto-ethnography on affective citizenship in the techno electronic dance music scene. (August 2016) - Zebracki, Martin
Abstract: This study examines auto-ethnographical experience with bodily participation in spaces of techno electronic dance music (EDM). The article engages with how inner- and inter-corporeal lived experience in techno-space constructs affective citizenship on the very personal level of the participant-researcher. In this context, the article attends to the underexplored field of how affective citizenship is attained and valued along embodied knowledge of subcultural capital in the EDM scene. It particularly addresses its overlooked gendered/sexual and technologically mediated (e)motional body. Drawing on a feminist scholar-artist method, the article renders embodied encounters with techno-space through evocative vignettes that include affective writing, a drawing and introspective poetic revelation. This method aims to convey embodied knowledge of techno-space as creative transformative experience beyond conventional modes of retrospective narration. The article concludes with two key lived experiences of affective citizenship: first, at times the gendered/sexual and cyborgian body was mobilised into a state of emotionally shared publicness that co-produced techno-space. Second, (inter)actions in techno-space incited subcultural capital as a set of tacit knowledge assets (including affective, empathic and therapeutic qualities) to be accumulated over techno events and to be occasionally transferred to inclusive participation in the everyday life. Highlights: This auto-ethnographical study analyses affective citizenship via (e)motional participation in techno electronic dance music. Scholar-artist methods of affective writing, drawing and poetry aim to impart creative transformative experiences. The study examines how feelings in techno-space are mediated through the gendered/sexualised body and technology. Participation in techno-space accumulates tacit knowledge potentially useful to inclusive participation in the everyday life.